Estratégias matrimoniais da Casa de Bragança e o casamento do duque D. João II - Cunha, Mafalda Soares da (2010)
This article begins with an analysis of the long-term matrimonial strategies of the House of Braganza (1383-1640) with the end of determining and characterising the logic of their development. Next, it addresses some of the negotiating processes related to contracting marriage on the part of some members of the House, with the aim of making explicit the impact of changes in the political situation on the logic of alliances pursued by the ducal line of Braganza. In this context, the analysis of matrimonial alliances pursued after 1580 reveals both the loss of political status in comparison with the monarchy and the family s peripheral position on the international scene.